Navigating Content and Language Integrated Learning (CLIL) in Indonesian Universities: Promise and Pitfalls - Marhamah, Marhamah; Marhamah Marhamah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study explores the implementation of Content and Language Integrated Learning (CLIL) in Indonesian higher education, highlighting its benefits and challenges. CLIL is an instructional approach that integrates subject content with a foreign language, aiming to enhance both linguistic competence and academic achievement. While widely adopted in primary and secondary education, its application at the tertiary level presents distinct difficulties that require critical assessment. Using a synthesis research methodology, this study examines 15 empirical studies from reputable academic databases, including ERIC, Scopus, and ProQuest Education Journal. The findings reveal that CLIL improves students’ language skills, subject knowledge, and motivation. Additionally, it offers professional development opportunities for educators by refining their English proficiency and pedagogical strategies. However, several obstacles hinder CLIL’s effectiveness in Indonesian universities. Students’ limited English proficiency affects content comprehension, while a shortage of well-trained instructors poses instructional challenges. Further difficulties arise in integrating content with language instruction and developing appropriate assessment methods. This study emphasizes the necessity of institutional support, teacher training programs, and supplementary language courses to optimize CLIL’s benefits and mitigate its challenges. Future research should focus on targeted interventions to enhance its feasibility and sustainability in Indonesian higher education.